Talaromycosis in a renal transplant recipient returning from South China. Issue 1 (31st August 2020) - Vergidis, Paschalis; Rao, Anirudh; Moore, Caroline B.; Rautemaa‐Richardson, Riina; Sweeney, Louise C.; Morton, Muir; Johnson, Elizabeth M.; Borman, Andrew M.; Richardson, Malcolm D.; Augustine, Titus
Abstract: Talaromycosis is a fungal infection endemic in Southeast Asia. We report a case of a renal transplant recipient who developed infection after a trip to South China. She presented with constitutional symptoms and was found to have an FDG‐avid lung mass. Histopathology demonstrated small yeast cells and culture grew Talaromyces marneffei . The patient was treated with 2 weeks of liposomal amphotericin B followed by itraconazole. The dose of tacrolimus was significantly reduced because of the interaction with itraconazole. Mycophenolate mofetil was discontinued. After 12 months of treatment, the mass had completely resolved. Talaromycosis has mainly been reported in patients with AIDS and is uncommon among solid organ transplant recipients. The immune response against T. marneffei infection is mediated predominantly by T cells and macrophages. The diagnosis may not be suspected outside of endemic areas. We propose a therapeutic approach in transplant patients by extrapolating the evidence from the HIV literature and following practices applied to other endemic mycoses.